Immunohistochemical study of the muscularis externa of the esophagus in achalasia patients. Issue 1 (6th February 2012) - Hoshino, M.; Omura, N.; Yano, F.; Tsuboi, K.; Kashiwagi, H.; Yanaga, K.
Summary The etiology of achalasia is believed to be the neuropathy associated with chronic inflammation of the nerve plexus, but the cause of plexus inflammation is unknown. The purpose of this study was to evaluate the pathophysiology of achalasia by examining the muscularis externa of the esophagus. We used the muscularis externa of the esophagus of 62 patients with achalasia (median 44 years, male&nbsp: female 32:30) who underwent surgical treatment (achalasia group) and of 10 patients (median 65.5 years, male&nbsp: female 9:1) who underwent esophagectomy for thoracic esophageal cancer (control group) to perform immunohistochemical staining with S‐100, CD43, c‐kit (CD117), n‐NOS, vasoactive intestinal polypeptide (VIP), and ubiquitin. The cell counts that were positive for S‐100, n‐NOS, VIP, and ubiquitin were significantly lower in the achalasia group compared with the control group (P < 0.001, P= 0.001, P < 0.001, and P= 0.001, respectively). There were no statistically significant differences with respect to CD43 and c‐kit staining (P= 0.586 and P= 0.209, respectively). In conclusion, the pathophysiology of achalasia is therefore considered to be an impaired production of NO and VIP, which both affect interstitial cell of Cajal and smooth muscles, and this impairment is therefore considered to play a role in the pathophysiology of achalasia.